A dynamic systems theory approach to development of listening strategy use and listening performance. (December 2016) - Dong, Jihua
Abstract: This study investigated the developmental trajectories of an EFL learner's listening strategy use and listening performance and explored the dynamic correlation between the two variables from a dynamic systems perspective. A Chinese EFL learner's listening strategy use and listening performance were traced and examined every two weeks over a forty-week span. The data were analyzed using dynamic systems techniques including the moving min-max graph, Loess smoothing, variability, Monte Carlo technique, spline interpolation, moving window correlation and linear regression. It was found that the learner's listening strategy use and listening performance showed non-linear developmental patterns; regression in listening performance could predict progress to some extent; and the proximity of a new phase was characterized by great fluctuations and variability; there was a downward trend in the relationship between listening strategy use and listening performance over the study period. The analysis of the dynamic complex developmental path of individual listening strategies suggests a simplification, self-organization and self-adaptation process. The developmental patterns and dynamic correlations can provide insights into the interaction between listening strategies and listening performance in a dynamic system. The findings have valuable implications for theory construction and pedagogical practice relating to the development of listening strategies and performance.